2014
DOI: 10.12952/journal.elementa.000027
|View full text |Cite
|
Sign up to set email alerts
|

A characterization of Arctic aerosols on the basis of aerosol optical depth and black carbon measurements

Abstract: Aerosols, transported from distant source regions, influence the Arctic surface radiation budget. When deposited on snow and ice, carbonaceous particles can reduce the surface albedo, which accelerates melting, leading to a temperature-albedo feedback that amplifies Arctic warming. Black carbon (BC), in particular, has been implicated as a major warming agent at high latitudes. BC and co-emitted aerosols in the atmosphere, however, attenuate sunlight and radiatively cool the surface. Warming by soot deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
83
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 95 publications
(179 reference statements)
13
83
0
2
Order By: Relevance
“…For overflight 4, two temperature inversions were recorded between 2500 and 3000 m. The temperature inversions and the different shapes of the PNSDs are indicative of the presence of different air masses during overflight 4, although air mass back trajectories that arrived at 1000, 2000 and 3000 m indicate an air mass origin over the North Pacific for all three heights. Stone et al (2014) explain that layering of Arctic aerosol, as we observed it during overflight 4, is a function of where the aerosol particle sources are located. Thereby the crucial factors are the different pathways of aerosol transport in the lower Arctic troposphere.…”
Section: Comparison Of Height-resolved Airborne and Ground-based Pnsdsmentioning
confidence: 54%
“…For overflight 4, two temperature inversions were recorded between 2500 and 3000 m. The temperature inversions and the different shapes of the PNSDs are indicative of the presence of different air masses during overflight 4, although air mass back trajectories that arrived at 1000, 2000 and 3000 m indicate an air mass origin over the North Pacific for all three heights. Stone et al (2014) explain that layering of Arctic aerosol, as we observed it during overflight 4, is a function of where the aerosol particle sources are located. Thereby the crucial factors are the different pathways of aerosol transport in the lower Arctic troposphere.…”
Section: Comparison Of Height-resolved Airborne and Ground-based Pnsdsmentioning
confidence: 54%
“…The lifetime of SO 2 in the Arctic is more than 1 week (Thornton et al, 1989), and this means that SO 2 potentially acts as a reservoir from which new anthropogenic aerosols could form. Long-range transport of anthropogenic sulfur dominates in the Arctic winter and early spring because of the stable atmosphere and weak removal of particles, and concentrations significantly decrease during summer because of a lower number of sources within the polar front and stronger scavenging (Quinn et al, 2002;Stone et al, 2014). The backward configuration modeling of FLEXPART-WRF shows that potential emissions originated from the east for the first 2 days (12 and 13 July), and expanded to cover a broader region after that (Fig.…”
Section: Anthropogenic and Biogenic Sulfatementioning
confidence: 98%
“…The Arctic Ocean is considered a source of primary aerosol, such as sea salt and organics, as well as secondary particles from the oxidation of SO 2 to sulfate (SO 5192 R. Ghahremaninezhad et al: Biogenic, anthropogenic and sea salt sulfate size-segregated aerosols Sulfate in the Arctic atmosphere originates from anthropogenic, sea salt and biogenic sources. Anthropogenic aerosols, with a winter-to-springtime maximum known as Arctic haze, contain particulate organic matter, nitrate, sulfate and black carbon which originate from North America and Eurasia Quinn et al, 2002;Stone et al, 2014). Sea salt enters the atmosphere via mechanical processes such as sea spray and bubble bursting (Leck and Bigg, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Stone et al (2014;their Fig. 5) notes that only one aircraft campaign in the last 30 years occurred outside the Arctic Haze period.…”
mentioning
confidence: 99%